IMPLEMENTASI AKAD MURABAHAH PADA PEMBIAYAAN KEPEMILIKAN RUMAH DI BANK MUAMALAT KC DEPOK - Limbong, Elviyani; Subali (Al-Mashrafiyah (Jurnal Ekonomi, Keuangan dan Perbankan Syariah), 2024)
This study explores the implementation of the Murabahah Agreement for home ownership financing at Bank Muamalat KC Depok through field research employing qualitative methods. Data collection involved observation, interviews with staff and customers, and documentation review from relevant literature and books. The analysis utilized descriptive techniques, examining primary and secondary data sources. Findings indicate that Bank Muamalat KC Depok adheres to the Fatwa of the National Sharia Council of the Indonesian Ulema Council No. 04/DSN-MUI/IV/2000 on Murabahah, ensuring each stage of the agreement aligns with Islamic principles and conditions specified in the Fatwa. The study confirms that the bank effectively implements Islamic law in its KPR iB Hijrah financing, complying with regulatory standards.